Kerusakan Jalan Pada Jalan Maredan Kecamatan Tualang Kabupaten Siak Dengan Metode Pavement Conditon Index (PCI) STA 41+770 – STA 46+770 - Munziri; Winayati; Rahmat, Hendri (JURNAL TEKNIK UNILAK, 2023)
Jalan Maredan is one of the access roads to Perawang Village which is located in Maredan Village, Tualang District, Siak Regency, Riau Province. The road was severely damaged, especially at STA 41+770 to STA 46+770, there were many types of road damage, such as potholes, subsidence, longitudinal cracks, and crocodile skin cracks. The purpose of this study was to determine the level of road damage on Jalan Maredan, Tualang District, Siak Regency, STA 41+770 to STA 46+770 using the Pavement Condition Index method and how to handle each road damage. From the results of the analysis, it was found that the accumulative PCI value starting from STA 41+770 to STA 46+770 was 35,78 % and the pavement condition was in poor condition. As for the handling that can be done in overcoming road damage, it is necessary to carry out routine road maintenance, periodic road maintenance, road rehabilitation, or road reconstruction.